Exploring the dynamics of the quality of HIV care experienced by female sex workers living in the Dominican Republic. - Tahilin Sanchez Karver; Clare Barrington; Yeycy Donastorg; Martha Perez; Hoisex Gomez; Kathleen R Page; David D Celentano; Katherine Clegg Smith; Deanna Kerrigan (Public Library of Science (PLoS), 2023)
Despite increased attention and efforts to improve HIV care among female sex workers (FSWs), they continue to have suboptimal HIV outcomes. Exploring the socio-structural dynamics related to the quality of HIV care received by FSWs is critical to further strengthen interventions to improve their HIV care continuum outcomes. In this study, we conducted two rounds of qualitative in-depth interviews with 20 FSWs living with HIV in the Dominican Republic to explore how healthcare experiences contributed to their quality of HIV care. Data was analyzed using a thematic analytic approach exploring diverse structural and relational aspects of the quality of HIV care affecting FSWs as they navigate the clinic environment. Results indicated that quality of HIV care was influenced by both structural and relational factors within clinics. At the structural level, insufficient stock of antiretroviral therapy and the financial burden created by HIV care related costs hindered FSWs' satisfaction with their current HIV care and presented a barrier in FSWs' ability to access HIV care services. Quality of care was also closely linked to relational aspects of the HIV care environment, including FSWs' relationship and communication with their clinical providers, as FSWs often expressed their satisfaction with HIV care experiences based on these interpersonal factors. Lastly, personal agency emerged as an important factor contributing to the quality of HIV care, specifically as FSWs' treatment literacy resulted in greater advocacy and demands for quality care. Programmatic efforts should be directed to improving the quality of HIV care experiences of FSWs in the clinic environment. These include addressing resource shortages, promoting positive and effective patient-provider relationships, and facilitating HIV treatment education opportunities for FSWs.